Benzosuberone as Precursor for Synthesis of Antimicrobial Agents: Synthesis, Antimicrobial Activity, and Molecular Docking. (14th September 2021) - Althagafi, Ismail; Farghaly, Thoraya A.; Abbas, Eman M. H.; Harras, Marwa F.
Abstract: Based on the wide range of various biological activities of benzosuberone derivatives and the emergence of multidrug resistance (MDR) of the continued use of antibiotics among different breeds microorganisms, we synthesized herein a new series of benzosuberone derivatives via the reaction of 6-((5-methylfuran-2-yl)methylene)-6, 7, 8, 9-tetrahydro-5 H -benzo[7] annulen-5-one with nuecluophilic nitrogen compounds and hydrazonoyl halides. The structures of the new compounds were elucidated based on their IR, 1 H-NMR and Mass spectra. Moreover, the potency of these compounds as antimicrobial agents has been evaluated. The results showed that some of the products have high activity exceed the used standard antibiotic. Additionally, the docking study was done to get the binding mode of the synthesized compounds with the binding site of the topoisomerase II enzyme. The results of molecular docking showed that the most active six derivatives are capable to fit in the binding pocket of topoisomerase II with binding energies ranging from –4.61 to –6.16 Kcal/mol.